Relationship between the Clinical Characteristics and Intervention Scores of Infants with Apparent Life-threatening Events - Choi, Hee Joung; Kim, Yeo Hyang (Journal of Korean medical science, 2015)
We investigated the clinical presentations, diagnostic and therapeutic modalities, and prognosis from follow-up of infants with apparent life-threatening events (ALTE). In addition, the relationship between the clinical characteristics of patients and significant intervention scores was analyzed. We enrolled patients younger than 12 months who were diagnosed with ALTE from January 2005 to December 2012. There were 29 ALTE infants with a peak incidence of age younger than 1 month (48.3%). The most common symptoms for ALTE diagnosis were apnea (69.0%) and color change (58.6%). Eleven patients appeared normal upon arrival at hospital but 2 patients required cardiopulmonary resuscitation during the initial ALTE. The most common ALTE cause was respiratory disease, including respiratory infection and upper airway anomalies (44.8%). There were 20 cases of repeat ALTE and 2 cases of death during hospitalization. Four patients (15.4%) experienced recurrence of ALTE after discharge and 4 patients (15.4%) showed developmental abnormalities during the follow-up period. The patients with ALTE during sleep had lower significant intervention scores (P=0.015) compared to patients with ALTE during wakefulness and patients with previous respiratory symptoms had higher significant intervention scores (P=0.013) than those without previous respiratory symptoms. Although not statistically significant, there was a weak positive correlation between the patient's total ALTE criteria and total significant intervention score (Fig. 2, r=0.330, P=0.080). We recommend that all ALTE infants undergo inpatient observation and evaluations with at least 24 hr of cardiorespiratory monitoring, and should follow up at least within a month after discharge.